Individuals’ usage of smoking cessation online health communities - Li, Chenglong (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2022)
Smoking is still a significant threat to human health. To reduce the prevalence of smoking, the World Health Organization (WHO) has highlighted the importance of offering help to quit tobacco use. Recently, smoking cessation online health communities (OHCs) have become an important online tool to help smokers kick their smoking habits. Smoking cessation OHCs are collectives of people who communicate with each other about quitting smoking through dedicated sites on the Internet. These OHCs offer substantial benefits to users, such as enriching their medical knowledge, enhancing their emotional comfort, reducing their stress, and improving their smoking cessation performance. However, smoking cessation OHCs face the great challenge of low levels of participation. Many users only visit these OHCs once and never return, despite the benefits. To improve the longevity of such OHCs and unleash their full potential, therefore, it is imperative to understand what motivates users’ continued usage of online smoking OHCs, and what prompts them to contribute knowledge to theseOHCs. Retaining users and knowledge-sharing have been central topics for Information Systems (IS) researchers studying post-adoption stage of OHC usage. However, few studies have investigated users’ post-adoption behaviors in the specific context of smoking cessation OHCs. Extant literature has focused primarily on the technology perspective of smoking cessation OHCs and ignored their inherent social factors (such as social support and social capital). An understanding of the interplay of social and technical beliefs that might explain behavioral intentions in this context remains obscure. This study examines the determining factors of two forms of IS post-adoption behaviors in the context of smoking cessation OHCs: the continuance intention and knowledge-sharing. A mixture of quantitative survey research and qualitative interview research is employed in this study. The quantitative method was used to answer research questions about the determinants of both continuance intention and knowledge-sharing. The qualitative approach was adopted to further examine what determines users’ continuance intention toward smoking cessation OHCs. The empirical data in this study was collected from individual users of smoking cessation OHCs in China and Finland. The results show that continuance intentionis influenced by users’ systems-related beliefs (e.g., perceived usefulness), by their social-related beliefs (e.g., perceived informational support, perceived emotional support, and perceived companionship), and by their knowledge-sharing behaviors. Similarly, knowledge-sharing is determined by users’ systems-related beliefs (e.g., perceived usefulness), by social-related beliefs (e.g., social ties and reciprocity), and by attitudes (e.g., satisfaction). In addition, users’ systems-related beliefs (e.g., perceived usefulness) were found to be affected by their social-related beliefs, such as perceived esteem support, perceived emotional support, shared language, shared vision, and commitment. This research contributes to the literature on IS post-adoption behaviors and smoking cessation OHCs. Specifically, it contributes to understanding individual users’ post-adoption behaviors by highlighting the impacts of different user beliefs and attitudes on two forms of IS usage. It sheds light on the roles of users’ systemsrelated beliefs (e.g., perceived usefulness), social-related beliefs (e.g., social support and social capital), and attitudes (e.g., satisfaction) in determining their usage behaviors. Additionally, it contributes to understanding users’ different beliefs by examining the relationships between them. The findings related to the impact of social-related beliefs on systems-related beliefs offer a comprehensive picture of the roles of different users’ beliefs in smoking cessation OHCs. Furthermore, it contributes to the literature on smoking cessation OHCs by offering insights into retaining users and motivating their knowledge contributions. The findings on the determinants of both continuance intention and knowledge-sharing extend understanding about how to design and maintain smoking cessation OHCs. From a practical view, this research has important implications for smoking cessation OHC managers, specifically regarding keeping the OHC active and sustainable via retaining users and encouraging them to share knowledge. It also helps smoking cessation intervention designers to develop successful and sustainable digital interventions. By supporting the longevity of smoking cessation OHCs, these findings additionally offer implications to healthcare service providers regarding the needs of versatile smoking cessation assistance and support.

Tupakointi on suuri uhka ihmisten terveydelle. Tupakoinnin vähentämiseksi Maailman terveysjärjestö (World Health Organization,WHO) on korostanut tupakoinnin lopettamisen avun antamisen merkitystä. Viime aikoina tupakoinnin lopettamiseen liittyvät terveysverkkoyhteisöt (online health communities, OHCs) ovat muodostuneet tärkeiksi verkkotyökaluiksi tupakoinnin lopettamisessa. Tupakoinnin lopettamisen verkkoyhteisöt ovat Internetissä olevia tarkoituksellisia yhteisöjä ihmisille jotka kommunikoivat keskenään tupakoinnin lopettamisesta. Nämä verkkoyhteisöt tarjoavat merkittäviä etuja käyttäjilleen, kuten lääketieteellisen tietämyksen lisääntyminen, henkisen hyvinvoinnin lisääntyminen, stressin vähentäminen, ja tupakoinnin lopettamisen tuloksellisuuden vahvistaminen. Kuitenkin tupakoinnin lopettamisen verkkoyhteisöt kärsivät alhaisesta osallistumisaktiivisuudesta. Monet käyttäjät käyvät yhteisöissä kerran eivätkä koskaan palaa, hyödyistä huolimatta. Tupakoinnin lopettamisen verkkoyhteisöjen jatkuvuuden kehittämiseksi ja täyden hyödyn realisoimiseksi on välttämätöntä ymmärtää mikä motivoi käyttäjiä jatkamaan käyttöä, ja mikä rohkaisee heitä tuottamaan tietämystä näihin verkkoyhteisöihin. Käyttäjien säilyttäminen ja tietämyksen jakaminen ovat olleet keskeisiä tietojärjestelmätieteen tutkimusteemoja tutkittaessa terveyden verkkoyhteisöjen käyttöä. Kuitenkin vain harvat tutkimukset ovat selvittäneet käyttäjien käyttöönoton jälkeistä käyttäytymistä juuri tupakoinnin lopettamisen verkkoyhteisöissä. Olemassa oleva kirjallisuus on keskittynyt pääosin tupakoinnin lopettamisen verkkoyhteisöjen tekniikkaan ja laiminlyönyt niihin oleellisesti liittyvät sosiaaliset tekijät (kuten sosiaalinen tuki ja sosiaalinen pääoma). Tällaisessa yhteydessä sosiaalisten ja teknisten tekijöiden vuorovaikutukseen liittyvä ymmärrys jää epämääräiseksi. Tämä tutkimus tarkastelee määrittäviä tekijöitä kahdelle tietojärjestelmien käyttöönoton jälkeiselle käyttäytymiselle tupakoinnin lopettamisen verkkoyhteisöjen puitteissa: käytön jatkamisen aikomus ja tietämyksen jakaminen. Tässä tutkimuksessa käytetään sekä kvantitatiivista kyselytutkimusta että kvalitatiivista haastattelututkimusta. Kvantitatiivista metodia käytettiin vastaamaan tutkimuskysymyksiin koskien sekä käytön jatkamisen aikomusta että tiedon jakamista. Kvalitatiivista lähestymistapaa käytettiin edelleen tarkentamaan mikä määrittää käytön jatkamisen aikomusta tupakoinnin lopettamisen verkkoyhteisöissä. Tämän tutkimuksen empiirinen data kerättiin yksittäisiltä käyttäjiltä tupakoinnin lopettamisen verkkoyhteisöissä Kiinassa ja Suomessa. Tulokset osoittavat, että käyttäjän tietojärjestelmään liittyvät uskomukset (esim. koettu hyödyllisyys) ja sosiaaliseen yhteisöön liittyvät uskomukset (esim. koettu tuki informaation muodossa, koettu emotionaalinen tuki, koettu kumppanuus) ja käyttäjien tiedon jakamiseen liittyvä käyttäytyminen vaikuttavat käytön jatkamisen aikomukseen. Samalla tavalla, tietämyksen jakaminen määrittyy tietojärjestelmään liittyvien uskomusten (esim. koettu hyödyllisyys) ja sosiaaliseen yhteisöön liittyvien uskomusten (esim. sosiaaliset siteet ja vastavuoroisuus) sekä mielipiteiden (esim. tyytyväisyys) kautta. Lisäksi käyttäjien sosiaalisen yhteisöön liittyvien uskomusten (esim. koettu kunnioitukseen liittyvä tuki, koettu emotionaalinen tuki, jaettu kielenkäyttö, jaettu visio ja sitoutuminen) havaittiin vaikuttavan käyttäjien tietojärjestelmän liittyviin uskomuksiin (esim. koettu hyödyllisuus). Tämä tutkimus tuottaa tietoa tietojärjestelmätieteen kirjallisuuteen tietojärjestelmien omaksumisen jälkeisestä käytöksestä ja tupakoinnin lopettamisen verkkoyhteisöistä. Erityisesti se tuottaa tietoa omaksumisen jälkeisestä käytöksestä korostamalla erilaisia käyttäjien uskomuksia ja mielipiteitä kahden käyttäytymismuodon suhteen. Tutkimus valaiseen käyttäjien järjestelmään liittyvien uskomusten (esim. koettu hyödyllisuus), sosiaaliseen yhteisöön liittyvien uskomusten (esim. sosiaalinen tuki ja sosiaalinen pääoma) sekä mielipiteiden (esim. tyytyväisyys) roolia tietojärjestelmän käyttöönoton jälkeisessä käyttäytymisessä. Lisäksi se tuottaa tietoa käyttäjien erilaisista uskomuksista tutkimalla niiden välisiä yhteyksiä. Sosiaaliseen yhteisöön liittyviin uskomuksiin kohdistuvat tutkimustulokset tarjoavat kattavan kuvan erilaisten käyttäjien uskomuksien merkityksestä koskien tupakoinnin lopettamisen verkkoyhteisöjä. Edelleen tutkimus antaa panoksensa tupakoinnin lopettamisen verkkoyhteisöjä koskevaan kirjallisuuteen tarjoamalla näkökulmaa siihen miksi tietyt käyttäjät pysyvät pitkään verkkoyhteisössä, ja mikä motivoi heitä antamaan tietämyksensä tarjolle. Sekä käyttämisen jatkumiseen että tiedon jakamiseen liittyviin syihin kohdistuvat tutkimustulokset laajentavat ymmärrystämme siitä kuinka suunnitella ja pitää yllä tupakoinnin lopettamisen verkkoyhteisöjä. Käytännön näkökulmasta tutkimuksella on tärkeitä johtopäätöksiä tupakoinnin verkkoyhteisöjen hallinnoijille, erityisesti siihen kuinka pitää yhteisö aktiivisena ja kestävänä säilyttämällä jäsenet ja rohkaisemalla heitä jakamaan tietämystä. Tutkimus myös auttaa tupakoinnin lopettamisen toimenpiteiden suunnittelijoita tuottamaan onnistuneita ja kestäviä interventioita. Tukemalla tupakoinnin lopettamisen verkkoyhteisöjen pitkäikäisyyttä nämä tutkimustulokset tarjoavat näkökulmia terveydenhuollon palveluiden tuottajille tupakoinnin lopettamisen liittyvään monimuotoiseen avustamiseen ja tukeen.